2020
DOI: 10.1017/s1355617719001449
|View full text |Cite
|
Sign up to set email alerts
|

Informant Reporting in Mild Cognitive Impairment: Sources of Discrepancy on the Functional Activities Questionnaire

Abstract: Objective:Relative to dementia, little is known about informant bias in mild cognitive impairment (MCI). We investigated the influence of informant demographic and relational characteristics on reports of everyday functioning using the Functional Activities Questionnaire (FAQ).Method:Four thousand two hundred eighty-four MCI participants and their informants from the National Alzheimer’s Coordinating Center Uniform Data Set were included. Informants were stratified according to cohabitation, relationship, visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 66 publications
2
25
1
Order By: Relevance
“…Previous studies have shown that study partners report a decline in IADL in preclinical AD, even before cognitive problems can be detected by the standard cognitive testing ( Sperling et al, 2011 ; Marshall et al, 2012 , 2017 ; Zoller et al, 2014 ). Due to impairments in awareness in persons with dementia ( Hanseeuw et al, 2020 ), (I)ADL functioning has traditionally been assessed using study partner-report questionnaires ( Loewenstein et al, 2001 ; Howorth and Saper, 2003 ; Wadley et al, 2003 ; Desai et al, 2004 ; Farias et al, 2005 ; Graham et al, 2005 ; Sikkes et al, 2009 ; Hackett et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that study partners report a decline in IADL in preclinical AD, even before cognitive problems can be detected by the standard cognitive testing ( Sperling et al, 2011 ; Marshall et al, 2012 , 2017 ; Zoller et al, 2014 ). Due to impairments in awareness in persons with dementia ( Hanseeuw et al, 2020 ), (I)ADL functioning has traditionally been assessed using study partner-report questionnaires ( Loewenstein et al, 2001 ; Howorth and Saper, 2003 ; Wadley et al, 2003 ; Desai et al, 2004 ; Farias et al, 2005 ; Graham et al, 2005 ; Sikkes et al, 2009 ; Hackett et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the OAs themselves could have had better insight into their own capabilities than the informants. In general, informant- and self-report-based accounts of functional abilities may differ, for example, because the individual may lack insight, or the peer (or the individual) overestimates the problems’ severity due to stress and depression (e.g., Hackett, Mis, Drabick, & Giovannetti, 2020 ; Jorm et al., 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to impairments in awareness in persons with dementia (5), (I)ADL functioning has traditionally been assessed using study partner-report questionnaires (6)(7)(8)(9)(10)(11)(12)(13)(14). However, it has been suggested that study partner-report may be influenced by study partner depression, anxiety and caregiver burden (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%